2007
DOI: 10.1063/1.2723116
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarizability of GaAs dimer is not negative

Abstract: We present a systematic study of the static electric hyperpolarizability of Ga(2)As(2). The authors rely on finite-field high-level ab initio calculations with carefully optimized basis sets. Their best values for the mean and the anisotropy of the dipole polarizability are alpha=158.57 and Deltaalpha=130.33e(2)a(0) (2)E(h) (-1). For the hyperpolarizability we propose an estimate gamma=(155+/-15)x10(3)e(4)a(0) (4)E(h) (-3), which does not agree with the negative value predicted by Lan et al. [J. Chem. Phys. 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 27 publications
2
33
1
Order By: Relevance
“…The construction of molecule-specific, purpose-oriented basis sets for large molecular architectures or low-symmetry polyatomics is largely impractical. Nevertheless, previous work shows that for systems of reasonable size as atoms [23,53], atomic anions or cations [54,55], diatomics [56,57] and triatomics [58][59][60][61], symmetric polyatomics [62][63][64], and clusters [65][66][67][68], one can easily control the construction of the basis set in order to obtain suitable basis sets for electric property calculations.…”
Section: Electric Properties Of Atoms Molecules and Clusters Basicmentioning
confidence: 99%
“…The construction of molecule-specific, purpose-oriented basis sets for large molecular architectures or low-symmetry polyatomics is largely impractical. Nevertheless, previous work shows that for systems of reasonable size as atoms [23,53], atomic anions or cations [54,55], diatomics [56,57] and triatomics [58][59][60][61], symmetric polyatomics [62][63][64], and clusters [65][66][67][68], one can easily control the construction of the basis set in order to obtain suitable basis sets for electric property calculations.…”
Section: Electric Properties Of Atoms Molecules and Clusters Basicmentioning
confidence: 99%
“…Although the construction of purpose-oriented basis sets for polarizability calculations has been the object of several investigations [51][52][53][54][55], there are no reliable criteria for the choice of basis sets in theoretical predictions of electric hyperpolarizabilities. Previous experience shows that for atoms [56][57][58][59], diatomics [60][61][62], triatomics [63][64][65], and small polyatomics [66][67][68][69], it is possible to design basis sets by systematically augmenting reliable substrates of GTFs. Different strategies must be adopted in the case of clusters [70] or sequences of clusters [71][72][73][74].…”
Section: Computational Strategymentioning
confidence: 99%
“…In light of previous research [63][64][65][66], Maroulis et al determined the level of calculation needed to compute accurate cluster polarizability values; their results showed that the DFT method can provide reasonable values. The effects of the basis set on cluster polarizability were also discussed by the group of Maroulis [66][67][68][69].…”
Section: Polarizabilitymentioning
confidence: 97%
“…The effects of the basis set on cluster polarizability were also discussed by the group of Maroulis [66][67][68][69]. We obtained the polarizabilities of our systems with the same basis set as used for the optimizations, so that the calculations required were not excessively time-consuming.…”
Section: Polarizabilitymentioning
confidence: 99%